2020
DOI: 10.1055/s-0040-1701449
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Naive Surgeons and Opioid-Tolerant Patients: Can Education Alter Prescribing Patterns to Total Knee Arthroplasty Patients?

Abstract: Patterns of opioid overprescribing following arthroplasty likely developed given that poor pain control can diminish patient satisfaction, delay disposition, and lead to complications. Recently, interventions promoting responsible pain management have been described, however, most of the existing literature focuses on opioid naive patients. The aim of this study was to describe the effect of an educational intervention on opioid prescribing for opioid-tolerant patients undergoing primary total knee arthroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Among the opioid‐naïve patients in this study, 73/356 (20%) used opioids postoperatively, which is very similar to the rate of 18% in the present study. Further, opioid use was very low among all 386 patients with 86.3% using 10 or fewer opioid pills through 3 months postoperatively [29]. Together, our findings and these data suggest that achieving opioid‐free or opioid‐minimal TKA may be possible in both opioid‐naïve and opioid‐experienced patients by expanding the window of multimodal pain management from the first 72 hours after surgery to 3 months after TKA and prescribing a low amount of opioids [28].…”
Section: Discussionmentioning
confidence: 99%
“…Among the opioid‐naïve patients in this study, 73/356 (20%) used opioids postoperatively, which is very similar to the rate of 18% in the present study. Further, opioid use was very low among all 386 patients with 86.3% using 10 or fewer opioid pills through 3 months postoperatively [29]. Together, our findings and these data suggest that achieving opioid‐free or opioid‐minimal TKA may be possible in both opioid‐naïve and opioid‐experienced patients by expanding the window of multimodal pain management from the first 72 hours after surgery to 3 months after TKA and prescribing a low amount of opioids [28].…”
Section: Discussionmentioning
confidence: 99%
“…Physician and patient accountability are essential components in combating opioid overuse, as prior studies have shown that educational interventions focused on raising awareness of opioid overprescribing in both physicians and patients can lead to a significant decrease in postoperative opioid prescriptions and consumption. 6 , 7 , 8 , 9 , 23 , 24 , 25 Notably, the implementation of ePrescribing was an isolated change—prescribers prior to the implementation were required to perform background checks through a state prescription drug monitoring program and this database cross-reference continued. The advent of ePrescribing also did not have associated confounders—such as new limits in the number of opioids prescribed or mandatory training.…”
Section: Discussionmentioning
confidence: 99%